Adrenomedullin Expression in the Developing Human Fetal Lung. (January 2014) - Ramos, Carlos G.; Sun, Xi; Johnson, Eric B.; Nelson, Harold E.; Gonzalez Bosc, Laura V.
Background: Adrenomedullin (AM) is a vasodilator peptide produced by endothelial and smooth muscle cells in the systemic and pulmonary circulation. It promotes angiogenesis and alveolar growth and has protective effects in the cardiovascular and respiratory systems. Adrenomedullin's role in human pulmonary vascular and alveolar development is unknown. Objective: To test the hypothesis that AM is expressed during normal human lung development and that its expression changes with advancing gestational age by investigating the messenger RNA and protein expression of AM and its receptor components, calcitonin-receptorlike receptor (CRLR), receptor activity–modifying protein (RAMP)2, and RAMP3 in human fetal lung from 10 to 24 weeks of gestation. Methods: The gene expression of AM, CRLR, RAMP2, and RAMP3 was measured with real-time reverse-transcription polymerase chain reaction. Adrenomedullin protein expression was measured with Western blot. Immunohistochemical analyses of sections of lung tissue were performed. Statistical analysis was performed using linear regression and one-way analysis of variance followed by the Tukey range test. Results: Adrenomedullin, CRLR, RAMP2, and RAMP3 transcripts were expressed in the midgestation human fetal lung. The gene expression of AM, CRLR, and RAMP2 increased with increasing gestational age, whereas the gene expression of RAMP3 decreased. Adrenomedullin protein expression increased with increasing gestational age. Conclusion: Adrenomedullin is expressed in the midgestation human fetal lung and its gene and protein expression increased with increasing gestational age, suggesting a role for AM in human lung development. Supporting this conclusion, the AM1 receptor components CRLR and RAMP2 gene expression also increased with increasing gestational age. Conversely, the expression of RAMP3, a structural component of the AM2 receptor, decreased with increasing gestational age, suggesting different functions for the AM receptors in human fetal lung, as it has been demonstrated in animal models. This speculation requires further investigation.